Comparison of the effects of ovarian cauterization and gonadotropin-releasing hormone agonist and oral contraceptive therapy combination on endocrine-changes in women with polycystic ovary disease - Taskin, O; Yalcinoglu, AI; Kafkasli, A; Burak, F; Ozekici, U (Amer Soc Reproductive Medicine, 1996)
Objective: To study the effects of laparoscopic ovarian cauterization and combination of long-acting GnRH agonist (GnRH-a) and oral contraceptive (OC) therapy on endocrine changes in women with clomiphene citrate (CC)-resistant polycystic ovary disease (PCOD). Design: Prospective, randomized. Setting: University-based infertility clinic. Patients: Seventeen women with CC-resistant PCOD were included randomly in the study to either laparoscopic ovarian cautery or GnRH-a and OC therapy for 3 months. Main Outcome Measures: Serum concentrations of LH, FSH, androstenedione (A), T, and sex hormone-binding globulin (SHBG) were determined before each therapeutic approach and during the follicular phase of first menstrual cycle after the cessation of each treatment. Results: The mean. serum concentrations and the clinical profiles were similar in both groups. Both groups showed significant changes in LH, FSH, A, T, and SHBG compared with pretreatment levels. There were no significant differences in the final concentrations of LH, FSH, and A between the two study groups after each treatment, whereas T and SHBG levels were significantly different in the goserelin and OC group. The decrease in LH and increase in SHBG serum concentrations were greater in the goserelin and CC-treated women [-59% and +5.9% versus -70% and +13.5%, respectively]. Although the SHBG concentration increased in both groups, the serum SHBG concentration of the goserelin and OC group was significantly higher than the other group. Conclusion: Both therapeutic modalities revealed similar effects on the endocrine profiles in women with CC-resistant PCOD. Considering the invasiveness, cost, and potential complications of laparoscopic ovarian cauterization, noninvasive medical treatment with GnRH-a and OC combination may be more effective in restoring the optimal follicular environment in women with PCOD.
Keywords: laparoscopy; ovarian cautery; GnRH-a; polycystic ovary disease; oral contraceptive